Wadanan as a Manifestation of Harassing Face (Study of Conversational Implicature in Osing Language) - Sugiyantiningtyas, Titis (e-Journal of Linguistics, 2022)
Wadanan utterances were the research objects. The research problems were related to how the manifestation of harassing the face in wadanan utterances in the Osing language and the context of wadanan implicatures as a manifestation of harassing the face. The objectives of this study consisted of (1) to describe the manifestation of harassing face in wadanan utterances in the Osing language and (2) the context of wadanan implicatures as a manifestation of harassing face in the Osing language.The design of this study was qualitative descriptive. The data source was wadanan utterances in the Osing language. The data collection method of this study used direct observation with note-taking techniques. The procedure used in this study were: data presentation stage, data analysis, and data presentation from data analysis results. Wadanan utterances data obtained were presented descriptively.The results showed four manifestations of wadanan utterances harassing faces in the Osing language, namely with harsh words, with cynicism, ridicule, and expressions of disappointment, forbidding, and complaining.